If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -11x = 8 * 8 + 16 Multiply 8 * 8 13 + -11x = 64 + 16 Combine like terms: 64 + 16 = 80 13 + -11x = 80 Solving 13 + -11x = 80 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -11x = 80 + -13 Combine like terms: 13 + -13 = 0 0 + -11x = 80 + -13 -11x = 80 + -13 Combine like terms: 80 + -13 = 67 -11x = 67 Divide each side by '-11'. x = -6.090909091 Simplifying x = -6.090909091
| 21x=267 | | 2(10x+7)-x=-157 | | 5t^2+9t-19=0 | | (4x+2)-(5x+1)= | | 20-12i=5x+(4y)i | | 21x^2-7x=0 | | 3(k+3)=k-1 | | .8x^2-4x=0 | | 5y^2+50y=0 | | 0=5x^2-15x+20 | | -29+6x=-7+3(2x-7) | | 5=(-8)-t | | 6-k=14 | | -7a=-129-65 | | -11=n-2 | | 5x+4(-x+9)=41 | | h+6=13 | | 16x+6=-11 | | y=-.50*1-2 | | y=-.50*4-2 | | y=-.50*2-2 | | s=187+.22s | | 3x+3y=-24 | | (2x+25)*(x-1)=0 | | x+(x+1)=3x-5 | | 4x-2(4x+4)=-44 | | 9x+1.4=5.9 | | 7t-1.8=3.1 | | 4x-9.2=18.8 | | 14.80x+17y=91 | | 5p+0.8=20.8 | | 2r-5.3=10.7 |